Taxonomic review of Korean Siphonaria species (Mollusca, Gastropoda, Siphonariidae) - Yukyung Kim; Jina Park; Ui Wook Hwang; Joong-Ki Park (Biodiversity Data Journal)
Many molluscan species exhibit a high degree of shell morphological plasticity in their shape (including sculptures), size and colour patterns, which can vary significantly depending on environmental conditions. These shell morphological variations make it challenging to differentiate species, based on morphology alone, often resulting in various taxonomic errors, such as misidentifications, overlooking cryptic species diversity or a plethora of nominal species. The genus Siphonaria constitutes a significant component of the macrobenthic invertebrate fauna in intertidal habitats across temperate to tropical regions. Given the limited attention to shell variation in previous taxonomic studies on the Korean Siphonaria species, the extensive range of ecophenotypic shell variations documented in this group raises questions about the taxonomic validity of previously reported Siphonaria species in Korea.The present study provides a comprehensive taxonomic review of Korean Siphonaria species using a combination of shell morphology, radula structure and phylogenetic analysis of the mtDNA cox1 sequences. This integrative analysis confirmed the validity of S. acmaeoides, S. japonica and S. sirius in Korea, highlighting differences in shell and siphonal groove morphology amongst these species. Detailed descriptions of shell and radula characteristics, along with mtDNA cox1 sequences as DNA barcodes, are also provided, which are very useful for the accurate identification of Siphonaria species. Unlike these three Siphonaria species, the taxonomic validity of the four other species (S. coreensis, S. javanica, S. laciniosa and S. rucuana) previously reported from Korean waters is questionable, given their documented geographic distribution ranges and the potential misidentification of shell variants in Korean malacofaunal studies.